Age‐related aspects of human IgM+ B cell heterogeneity. Issue 1 (7th July 2015) - Martin, Victoria; Wu, Yu‐Chang; Kipling, David; Dunn‐Walters, Deborah K.
Abstract : The CD27 + IgD + B cell population, known as IgM memory, reduces with age. It is thought that this population is responsible for pneumococcal polysaccharide T‐independent responses, and that the age‐related reduction might be partially responsible for the increased susceptibility of older people to bacterial pathogens. There are other IgM + B cell populations that do not express IgD. We compared the different IgM populations using high‐throughput sequencing of the immunoglobulin (Ig) gene repertoire and multidimensional cell phenotyping and found that the different populations of IgM cells, defined by CD27 and IgD expression, have repertoire differences. Some of these differences are likely indicative of different selection pressures in an immune response, although the older individuals were found to have a changed repertoire in naive B cells, which may contribute to some of the changes seen in memory cells. In addition, even within the CD27 + IgD + IgM memory population there are multiple cell types. We show that the level of IgM expression varies substantially and hypothesize that this distinguishes between T‐dependent and T‐independent types of IgM memory cells. Significant age‐related changes in the relative proportions of these populations may exacerbate the reduction in T‐independent responders in old age.